Fast Na+ Kinetics and Suppressed Voltage Hysteresis Enabled by a High‐Entropy Strategy for Sodium Oxide Cathodes - Wang, Xian‐Zuo; Zuo, Yuting; Qin, Yuanbin; Zhu, Xu; Xu, Shao‐Wen; Guo, Yu‐Jie; Yan, Tianran; Zhang, Liang; Gao, Zhibin; Yu, Lianzheng; Liu, Mengting; Yin, Ya‐Xia; et al. (Advanced materials (Weinheim), 2024)
O3‐type layered transition metal cathodes are promising energy storage materials due to their sufficient sodium reservoir. However, sluggish sodium ions kinetics and large voltage hysteresis, which are generally associated with Na+ diffusion properties and electrochemical phase transition reversibility, drastically minimize energy density, reduce energy efficiency, and hinder further commercialization of sodium‐ion batteries (SIBs). Here, this work proposes a high‐entropy tailoring strategy through manipulating the electronic local environment within transition metal slabs to circumvent these issues. Experimental analysis combined with theoretical calculations verify that high‐entropy metal ion mixing contributes to the improved reversibility of redox reaction and O3–P3–O3 phase transition behaviors as well as the enhanced Na+ diffusivity. Consequently, the designed O3‐Na0.9Ni0.2Fe0.2Co0.2Mn0.2Ti0.15Cu0.05O2 material with high‐entropy characteristic could display a negligible voltage hysteresis (<0.09 V), impressive rate capability (98.6 mAh g−1 at 10 C) and long‐term cycling stability (79.4% capacity retention over 2000 cycles at 5 C). This work provides insightful guidance in mitigating the voltage hysteresis and facilitating Na+ diffusion of layered oxide cathode materials to realize high‐rate and high‐energy SIBs. High‐entropy configuration within transition metal slabs helps to strengthen TMO2 skeleton and enlarge the sodium ion diffusion channel, which promotes fast Na+ kinetics, reversible TM redox and phase transition as well as decreased voltage hysteresis, thus achieving impressive electrochemical performance for sodium oxide cathodes.